A case study evaluation of a Critical Care Information System adoption using the socio-technical and fit approach. Issue 7 (July 2015) - Yusof, Maryati Mohd.
Highlights Influencing factors of a Critical Care Information System adoption. A case study evaluation using a socio-technical and fit approach. Recommendations to improve the current system problems. Detail assessment of fits and misfits of the influencing factors.